2020
DOI: 10.1021/acs.energyfuels.0c00716
|View full text |Cite
|
Sign up to set email alerts
|

Wettability Indicator Parameter Based on the Thermodynamic Modeling of Chalk-Oil-Brine Systems

Abstract: The complex physicochemical interactions in the calcite-brine-crude oil system, triggered by the injection of modified salinity water (MSW) into the reservoir, are modeled by several researchers. However, the proposed models are either not consistent with a wettability alteration mechanism or cannot explain the observed improved oil recovery in chalk. We propose a new methodology denominated “Available Adsorption Sites” (AAS) that assesses the wettability alteration as a combined effect of a chemical and elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 116 publications
1
28
0
Order By: Relevance
“…However, the calcite site density of 4.95 sites/nm 2 is most commonly used in predicting electrokinetic properties of calcite surfaces. 11 , 21 , 26 , 27 , 31 , 34 , 63 , 66 , 67 Thus, it would be appropriate to determine the active site density of calcite surfaces through experimental approaches to correctly match the model prediction.…”
Section: Predicting Ionic Adsorption On Calcite Surfaces Using Dlm-ba...mentioning
confidence: 99%
“…However, the calcite site density of 4.95 sites/nm 2 is most commonly used in predicting electrokinetic properties of calcite surfaces. 11 , 21 , 26 , 27 , 31 , 34 , 63 , 66 , 67 Thus, it would be appropriate to determine the active site density of calcite surfaces through experimental approaches to correctly match the model prediction.…”
Section: Predicting Ionic Adsorption On Calcite Surfaces Using Dlm-ba...mentioning
confidence: 99%
“…The dependence of the modified salinity waterflooding (MSW) performance on site-specific conditions challenges not only the selection of suitable (oil field) candidates that could benefit from this enhanced oil recovery (EOR) but also the prediction of a “successful” water composition for a particular oil field. Several studies have tackled this problem by seeking a link between the interactions in the crude oil–brine–rock system, the wettability alteration, and eventually the additional oil recovery. Surface complexation models (SCMs) are commonly used to describe these interactions at both the oil–brine and calcite–brine , interfaces. SCMs can be used in combination with analytical or numerical ,, flow models for history matching purposes and eventually as predictive tools.…”
Section: Introductionmentioning
confidence: 99%
“…Main parameters defined in several SCMs reported in the literature: surface reactions (left), equilibrium constants (upper right), enthalpy of reaction (lower right). For further details on the models, the reader is referred to refs and (M1), ref (M2), ref (M3), ref (M4), ref (M5), and refs , , and (M6). Some models (M2, M3, and M5) do not directly report enthalpy of reactions but log K at several temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…Here, we consider that the adsorption of ions takes place essentially on the predominant {101̅4} calcite cleavage plane, characterized by an equal number of hydrated calcium and carbonates sites (4.95 #/nm 2 ) . Besides the surface reactions included in our previous publications, , i.e., de­(protonation) and the adsorption of calcite lattice ions (i.e., Ca 2+ and CO 3 2– ) or ions commonly present in seawater (e.g., Mg 2+ and SO 4 2– ), we define an explicit interaction between the calcite and carboxylate ion. Since we presume that the calcite surface is hydrated, only the carboxylates partitioned in the water phase can adsorb on the calcite surface; this is consistent with the observations from the work of Fathi et al Moreover, as previously indicated by several experimental studies, we postulate that carboxylates interact with the calcite calcium sites leading to the removal of the hydroxyl group upon adsorption.…”
Section: Methodsmentioning
confidence: 99%
“…However, none of these approaches considers an explicit interaction between the crude oil components and the calcite, which makes it impossible to quantify the polar components adsorbed on the mineral, which eventually governs the wettability condition. Moreover, in the previous models, the two interfaces are assumed to be independent (e.g., refs , , and ) as these models do not consider that some oil components partition between the oil and water phases, leading to changes not only in the pH but also calcite reactivity.…”
Section: Introductionmentioning
confidence: 99%